Simulation and Fabrication of Three-Layer SnO2/Ag/SnO2 Nanostructure Coating for Energy Storage - Esmail Shahriari; Morteza Raeisi; Sanaz Alamdari (Progress in Physics of Applied Materials)
In this work, the three-layer SnO2/Ag/SnO2 coating on the glass substrate was designed and the optimal thickness was calculated using Film Wizard software. Then the designed samples were fabricated using thermal evaporation technique. Analysis was conducted on optical, electrical, and thermal properties of the samples, including coefficient of merit, surface resistance, and optical transmittance and reflectance. The results showed that the three-layer structures, SnO2/Ag/SnO2, have the necessary and favorable conditions for use as heat insulating and energy saving coatings on glass windows. The optimal thickness was determined 20nm for silver and 70 nm for SnO2. The recorded optical transmission in the visible spectrum and the reflected light in the infrared spectrum are 79.66% and 88.66%, correspondingly. The surface electrical resistance of 11.69 Ω⁄sq has been obtained for the constructed system, which is a suitable value for this coating. The calculated optical values show that the heat transfer from sunlight is minimized through this coating and this coating can be used as a suitable energy storage.